2019
DOI: 10.1016/j.ibror.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A new inbred strain of Fawn-Hooded rats demonstrates mania-like behavioural and monoaminergic abnormalities

Abstract: The Fawn-Hooded (FH) rat carries a gene mutation that results in a dysfunctional serotoninergic system. However, previous studies have reported differing features between the FH/Wjd and FH/Har strains. We aimed to compare the behavioural and neurobiological features of FH/HamSlc rats with those of Fischer 344 rats. We performed the open field, elevated minus-maze, Y-maze spontaneous alternation, and forced swim tests to investigate behavioural alterations. We also assessed neurobiological characteristics by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…In line with this, Maddaloni et al (2018) showed that 5-HT depleted Tph2 mutant mice present an innate behavior resembling mania, which was reversed by mood stabilizer treatment (valproic acid) ( Maddaloni et al, 2018 ). Also, Azechi et al (2019) reported that Fawn-Hooded (FH) rats that carry dysfunctional gene mutations in the serotonergic system presented hyperactivity and high impulsivity behavior followed by low hippocampal 5-HT levels and increased 5-HT metabolization rate ( Azechi et al, 2019 ). On the other hand, the results obtained with our drug protocols revealed that DOXY had few effects against AMPH-induced 5-HT changes.…”
Section: Discussionmentioning
confidence: 68%
“…In line with this, Maddaloni et al (2018) showed that 5-HT depleted Tph2 mutant mice present an innate behavior resembling mania, which was reversed by mood stabilizer treatment (valproic acid) ( Maddaloni et al, 2018 ). Also, Azechi et al (2019) reported that Fawn-Hooded (FH) rats that carry dysfunctional gene mutations in the serotonergic system presented hyperactivity and high impulsivity behavior followed by low hippocampal 5-HT levels and increased 5-HT metabolization rate ( Azechi et al, 2019 ). On the other hand, the results obtained with our drug protocols revealed that DOXY had few effects against AMPH-induced 5-HT changes.…”
Section: Discussionmentioning
confidence: 68%